2008
DOI: 10.1103/physrevlett.101.142502
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Order-to-Chaos Region in SuperdeformedTb151andPb196Nuclei with Continuumet al.

Abstract: The γ−decay associated with the warm rotation of the superdeformed (SD) nuclei 151 Tb and 196 Pb has been measured with the EUROBALL IV array. Several independent quantities provide a stringent test of the population and decay dynamics in the SD well. A Monte Carlo simulation of the γ-decay based on microscopic calculations gives remarkable agreement with the data only assuming a large enhancement of the B(E1) strength at low excitation energy, which may be related to the evidence for octupole vibrations in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The experimental results, in terms of number of discrete excited bands of low-K and high-K nature, are interpreted via a simulation of the collective γ decay, based on microscopic cranked shell model (CSM) calculations at finite temperature [25,26]. This is a powerful tool to quantitatively describe nuclear structure properties of warm rotating nuclei, probing key aspects of their γ decay, as previously done in different regions of mass and deformation [20,[27][28][29][30][31]. It is anticipated that agreement between data and theory is obtained only by strongly quenching the decay strength of E1 statistical transitions between low-K and high-K discrete excited bands, resulting in reduced hindrance factors which follow the same trend, with excitation energy, as observed in spectroscopic studies of K isomers in the A ≈ 160-180 mass region [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results, in terms of number of discrete excited bands of low-K and high-K nature, are interpreted via a simulation of the collective γ decay, based on microscopic cranked shell model (CSM) calculations at finite temperature [25,26]. This is a powerful tool to quantitatively describe nuclear structure properties of warm rotating nuclei, probing key aspects of their γ decay, as previously done in different regions of mass and deformation [20,[27][28][29][30][31]. It is anticipated that agreement between data and theory is obtained only by strongly quenching the decay strength of E1 statistical transitions between low-K and high-K discrete excited bands, resulting in reduced hindrance factors which follow the same trend, with excitation energy, as observed in spectroscopic studies of K isomers in the A ≈ 160-180 mass region [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is found that the rotational damping width is smaller than the average distance d 2 between states, which interact via the residual two-body interaction. The ridges in Hg while they have a rather complex structure [79]. The number of bands however, is found to be smaller than in Hg 194 , as well as the fraction of the E2 strength found in the ridges, but the spin domain and excitation energy probed is quite different due to competition with fission and gating conditions and so, one cannot exclude that precursor-to-ergodic bands also exist in Pb 196 .…”
Section: Excited Superdeformed Statesmentioning
confidence: 86%
“…In particular, extensive work was done in connection with low-K/high-K structures, in order to investigate the transition between order and chaos in the atomic nucleus [51,67,[74][75][76]. In more recent yearstaking advantage of high statistics experiments with large arrays-statistical techniques have also become a powerful tool for a quantitative investigation of superdeformed configurations [46,[77][78][79][80][81][82][83] (the topic of the next section) and to The experimental average number of paths obtained from the fluctuation analysis of ridge structures in double and triple coincidence histograms (see figure 7), as a function of path length. The lines show predictions from the cranked shell model including a two-body residual interaction with different values of the interaction strength V 0 , as given in the legend.…”
Section: The Order-to-chaos Transition In the Atomic Nucleusmentioning
confidence: 99%
“…Making use of the accelerated heavy ions provided by the Legnaro linac and of modern γ-detector arrays designed to select high-multiplicity cascades of γ-rays, discrete nuclear states up to the fission limit have been identified in a large variety of nuclei. Beyond the region of discrete states, studies of the quasi continuum at high spin have brought information on the order-chaos transitions [14,15]. Particularly at LNL, in connection with superdeformation the problems of the feeding and decay-out of the SD bands in different mass regions have attracted much interest [16,17].…”
Section: Heavy-ion Reactions: Nuclear Structure At the Limits Of The ...mentioning
confidence: 99%